HEURISTIC METHOD OF SHIPS SELECTION FOR THE COORDINATED WORK OF WATER TRANSPORT - Shcherbina, O. V.; Shibaev, A. G. (Science and Transport Progress, 2021)
Purpose. The study aims to develop a formulation methodology for ship selection in the coordinated work of sea and river transport using a heuristic approach. Methodology. To realize the purpose set in the study, the authors carried out an analysis of domestic and foreign literature sources on the current topic, studied specifics and conditions for the effective operation of marine mono-hulled ships and composite tug/barge towing ones. Findings. The analysis results allowed formulating the heuristics methods that ensure the selection of the type sizes of tug/barge towing ships for the mixed «river-sea» navigation from the priority range of ships of the existing fleet. The proposed method makes it possible to select ships in a more appropriate manner according to the established scheme of work. Rational combinations of technical and operational characteristics of such pairs as «barges and tows», «tug/barge towing ship and sea-going ship», «tug/barge towing ship and restrictive characteristics of the area of navigation» are a prerequisite for the shipping company profit growth by increasing the capacity of ships. Originality. For the first time, the authors applied a heuristic approach to the selection of tug/barge towing ships and sea-going ones for coordinated work with the performance of cargo operations on the raid of the estuary port when transporting bulk goods. The basis of the approach is the selection of a rational mix of technical and operational characteristics of barges and tugs. The proposed approach allows determining the best combination of ship type sizes in the organization of coordinated work of sea and river transport. At the same time, the continuity of the goods transportation process from the sea ports to the river ones located in the depth of the country (and in the opposite direction) is ensured. Practical value. The presented methodology is a logical continuation of the cycle of studies performed by the authors. The obtained results will also be applied in subsequent personal research developments. In addition, the presented research may be useful for shipping companies that run the tug/barge towing fleet. The presented methodology may also be introduced into the learning process of transport higher education institutions in the study of relevant disciplines.